Monitoring of a French bat colony shown naturally infected by EBLV-1 from 2009-2012. Discovery of a new infection case in the colony three years after the first positive rabies diagnostic (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The passive surveillance of bat rabies was improved in France since 2000, thanks to a National bat rabies network constituted by Veterinary Services and bat handlers from the Chiroptera group (Société Française pour l’Etude et la Protection des Mammifères). To date,59 Eptesicus serotinus were shown infected by the European Bat Lyssavirus type 1 (EBLV-1) in France out of 950 cases reported throughout Europe. In the context of the passive surveillance, we reported for the first time in June 2009 in France, in the village of Ancy sur Moselle (located in the north east of the country), six positive cases in a colony of Eptesicus serotinus naturally shown infected by EBLV-1. The field studies, carried out from 2009-2012 on 186 tested bats with vaccinated bat specialists showed a fall of the seroprevalence by 5. In 2009, 45% blood samples were shown positive with a modified FAVNt adapted for bat micro-samples for the presence of neutralizing EBLV-1 antibodies against 8% in 2011. Three years after the first report of the EBLV-1 infection in the colony of Ancy Sur Moselle, a new positive case was reported into the reproduction colony at the end of July 2012. The colony was constituted by 80 bats in May and by 46 animals at the end of July. Similarly to 2009, the case was reported on a juvenile female and the isolated virus was EBLV-1b. Thanks to the education of bat workers to the risks of bat rabies, a new positive case was detected on July 23, 2012 in Eastern France on a Myotis naterreri. This species was recently shown infected by BBLV (Bokeloh Bat Lyssavirus) in Germany. To date, this is the first case reported in France on the species Myotis naterreri. This case was found in a village distant of 40 km from Ancy sur Moselle. The monitoring of the colony from Ancy sur Moselle with the results of field studies investigated from 2009- 2012 will be presented and discussed as well as the new case of infection diagnosed on Myotis naterreri.